THE REASONS OF INTENSIVE WEAR OF CYLINDERS OF YAMZ ENGINES – 238NB - S. A. Kornilovich (Вестник СибАДИ)
It is stated results of control in the course of repair of technical condition of cylinders of engines. Need of diagnosing of cylinders in structural parameters by direct measurements with partial or full dismantling of engines is proved. The description of an order of performance of direct measurements of cylinders, the formed wear forms, possible errors of a relative positioning of surfaces and axes of details of tsilindroporshnevy group, a crank – the conrod mechanism and their influence on process of wear of cylinders is made.